THE URBAN SYSTEM, CENTRALITIES AND THE USE OF URBAN SPACE IN MIDDLE CITIES - Sposito, Eliseu Saverio [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2023)
This text is structured in three parts. In the first, we present a discussion about the concept of center (downtown) and its role for the retail trade. Next, we discuss the formation of subcenters defining new centralities to show how the city restructures in response to changes at different scales, from the broader process of globalization to the localization of commercial activities, in a geographic articulation of scales. Finally, the displacement of people in their consumption actions shows how mobility presents itself in urban space. We have chosen, as case studies, the cities of Presidente Prudente, Ribeirao Preto and Marilia, each one with their specific characteristics that condition and are the product of the new relations of people in their choices of consumption. As partial result, we will demonstrate the following: 1) consumption is conditioned by the social class to which the individual belongs; 2) urban mobility (independent of means of transport) shapes the new centralities and modifies the role of the main center of the city; 3) the city restructures because of the locations that differ according to people's purchasing power. From the methodological viewpoint, the information was obtained indirectly and directly through field observation, questionnaires and interviews with different groups of people. As a way of visualizing the specific characteristics of the cities, we use cartographic representation.
Keywords: Urban system; Urban space; Middle city; Urban centrality